How Can the Pitching Research Framework Assist in Summarizing and Presenting Research Ideas? A Research Pitching Competition Story - Vu Nguyen Manh Hoai (Journal of Accounting and Management Information Systems (JAMIS), 2022)
This letter's main objective is to provide a unique insight into an application of the "pitching research" framework by Faff (2015,2021). In particular, it shows how the framework can be useful to help young researchers write concise academic literature even after they have come up with their own ideas. To further explore this claim, the author offers a personal reflection on how to use the framework to summarise a twenty-page-long research proposal down to a one-thousand-word summary which ended up winning him the 2022 InSPiR2eS Global Pitching Research Competition.
Keywords: O33; 650; Pitching Research; Blockchain Configuration; Framework; Framework; Financial Ecosystem